2004
DOI: 10.1144/0016-764903-077
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon-isotope stratigraphy recorded by the Cenomanian–Turonian Oceanic Anoxic Event: correlation and implications based on three key localities

Abstract: We present new, detailed carbon-isotope records for bulk carbonate, total organic carbon (TOC) and phytane from three key sections spanning the Cenomanian-Turonian boundary interval (Eastbourne, England; Gubbio, Italy; Tarfaya, Morocco), with the purpose of establishing a common chemostratigraphic framework for Oceanic Anoxic Event (OAE) 2. Isotope curves from all localities are characterized by a positive carbon-isotope excursion of c. 4‰ for TOC and phytane and c. 2.5‰ for carbonate, although diagenetic over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
400
2
18

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(444 citation statements)
references
References 23 publications
24
400
2
18
Order By: Relevance
“…A similar argument has been made for the isotopic data associated with the Oceanic Anoxic Events in the Cretaceous Period; that is, the deposition of black shales and sub-oxic conditions were regional but their effects on the marine δ 13 C record were global (e.g. Tsikos et al, 2004;Wagreich, 2009). We therefore conclude that the Lennard Shelf isotope record is a viable marine proxy that documents the extensive burial of organic carbon in other sedimentary basins around the world (North America, Europe, China, and North Africa).…”
Section: Discrepancy In Timingsupporting
confidence: 60%
“…A similar argument has been made for the isotopic data associated with the Oceanic Anoxic Events in the Cretaceous Period; that is, the deposition of black shales and sub-oxic conditions were regional but their effects on the marine δ 13 C record were global (e.g. Tsikos et al, 2004;Wagreich, 2009). We therefore conclude that the Lennard Shelf isotope record is a viable marine proxy that documents the extensive burial of organic carbon in other sedimentary basins around the world (North America, Europe, China, and North Africa).…”
Section: Discrepancy In Timingsupporting
confidence: 60%
“…The last occurrence of R. cushmani is correlated with the uppermost Cenomanian, which is equivalent to the basal horizon of the OAE2 interval ( Fig. 2c) [19][20][21][22][23] . The first occurrence of the calcareous nannofossil marker species Quadrum gartneri Prins and Perch-Nielsen, which occurs at the base of the Turonian and the upper part or just above the OAE2 interval ( Fig.…”
Section: Biostratigraphymentioning
confidence: 98%
“…A detailed bio-and carbon isotope-stratigraphic framework across the OAE2 interval has been determined for Pueblo (USA), Eastbourne (England), Tarfaya (Morocco), Wadi Bahloul (Tunisia), Provence (France) and Gubbio (Italy) [19][20][21][22][23] . These studies have revealed a detailed stratigraphic range of age-diagnostic marker species in macro-and microfossils across OAE2.…”
Section: Biostratigraphymentioning
confidence: 99%
“…The fact that this trend is also observed in Chrummflueschlucht, despite the obvious lack of anoxia during OAE 2, is an indication that the diminution in P burial rates is a global phenomenon (cf. Föllmi, 1995 (Jenkyns et al, 1994;Tsikos et al, 2004) and also with the section of Rehkogelgraben in the Ultrahelvetic unit (Wagreich et al, 2008). Oxygen stable isotopes in carbonates are more affected by diagenesis compared to carbon isotopes (Schrag et al, 1995), but the good agreement between Chrummflueschlucht and other sections of the northern Tethys indicates that the long-term variations in the d…”
Section: Paleoenvironmental Conditions In the Helvetic Realm During Omentioning
confidence: 98%
“…The lower part of the Co trend shows variations similar to As (with values between 1 and 6 ppm). In the second part of the section (from 20 m to the top), Co contents shows rather low values with a slight increase at w32 m. Mo contents remain quite constant along the entire section and deviate towards higher values only in the interval coeval with the decrease in d (Schlanger and Jenkyns, 1976;Jenkyns, 1980;Pratt and Threlkeld, 1984;Gale et al, 1993;Jenkyns et al, 1994;Leckie et al, 2002;Tsikos et al, 2004;Caron et al, 2006;Jarvis et al, 2006;Grosheny et al, 2006;Voigt et al, 2006Voigt et al, , 2007Mort et al, 2007;Takashima et al, 2010). The typical shape of the CeT boundary positive excursion, as observed in the GSSP section at Pueblo, Colorado (Pratt and Threlkeld, 1984;Sageman et al, 2006) Kingdom (Paul et al, 1999;Gale et al, 2005) is characterized by (1) a first increase in d…”
Section: Redox-sensitive Trace Elementsmentioning
confidence: 99%